2017
DOI: 10.4172/2157-7579.1000465
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Some Factors on Number of Services per Conception in Dairy Cows

Abstract: The study involved 55 685 Polish Holstein-Friesian cows whose services per conception (SPC) averaged 2.2. Statistical analysis performed using the GLM procedure of SAS, showed significant differences in SPC value within different factors. The greatest changes were associated with daily milk yield of the cows; as it increased from ≤ 20 kg to >40 kg, the number of services required to conceive increased by 0.6. SPC value deteriorated also with an increasing number of cows in the herd (by 0.37) and with an increa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
1
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 25 publications
0
5
1
4
Order By: Relevance
“…A shorter interval to first heat, lower number of SPC and the interval to conception in MgB cows indicate a possible association between improved fertility and prepartum Mg-butyrate supplementation. The number of SPC reported in the present study is higher than those reported by others for Holstein-Friesian cows [ 63 , 64 , 65 ]. This is due to the systematic selection for milk production in Hungary (over 11,200 kg/305 d corrected lactation) and the handling of fertility-related parameters as secondary traits by Hungarian cattle breeders.…”
Section: Discussioncontrasting
confidence: 89%
“…A shorter interval to first heat, lower number of SPC and the interval to conception in MgB cows indicate a possible association between improved fertility and prepartum Mg-butyrate supplementation. The number of SPC reported in the present study is higher than those reported by others for Holstein-Friesian cows [ 63 , 64 , 65 ]. This is due to the systematic selection for milk production in Hungary (over 11,200 kg/305 d corrected lactation) and the handling of fertility-related parameters as secondary traits by Hungarian cattle breeders.…”
Section: Discussioncontrasting
confidence: 89%
“…Siatka et al. (2017) showed SC value to decrease (by 0.11) with increasing somatic cell counts in milk. Also Gunay and Gunay (2008) reported that clinical mastitis in cows during the first 90 days of lactation had a negative effect on cow fertility (reproductive rest period, calving to conception interval and number of services per conception), because udder inflammation is the reason for changes in the concentration or activity of cortisol, PGF‐2α, GnRH, LH, FSH, progesterone, oestradiol, prolactin and many others.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies found a relationship between udder health and services per conception. Siatka et al (2017) showed SC value to decrease (by 0.11)…”
Section: Ta B L E 3 Number Of Splitting Rules and Importance Of Varia...mentioning
confidence: 97%
“…[ 7 ]. Furthermore, Polish studies by Siatka et al , 2017 [ 25 ] showed that early inseminations of cows after calving (<60 DPP) resulted in a higher number of services per conception than those made between 151 and 180 DPP (2.41 vs. 2.1 p<0.0001). Several authors have reported the consequences of energy deficit on fertility postpartum [ 26 ].…”
Section: Discussionmentioning
confidence: 99%